(untitled) (Global Journal of Science Frontier Research, 2015)
This study was carried out to conform the Nutrient availability and maize growth in soil amended with mineral fertilizer and biocompost. Biocompost is prepared from sugarcane filtercake and other waste material of sugarmills. The biocompost samples were collected from Sugar Mill, Matiari and analyzed for macro nutrients. The pot experiment was conducted with mineral fertilizer and biocompost amendment for maize crop. The pot experiment was replicated three times in a completely randomized block design. Pot experiment results revealed that there were pronounced positive effects of addition of biocompost. Maize crop data showed that the effect of biocompost and mineral fertilizers was non-significant with respect to N, P and K contents. Data describing the soil physical and chemical properties at the end of pot experiment under mineral fertilizers and biocompost showed that the EC values of post harvest samples increased with the application of biocompost while pH was not affected.